80.7k views
4 votes
Which phrase describes the algebraic expression 7/8y-3​

1 Answer

7 votes

Answer:

Step 1: Remove parentheses by multiplying factors.

= (x * x) + (1 * x) + (2 * x) + (2 * 1)

Step 2: Combine like terms by adding coefficients.

(x * x) = x2

(1 * x) = 1x

(2* x) = 2x

Step 3: Combine the constants.

(2 * 1) = 2

Step 4: Therefore, Simplifying Algebraic Expression is solved as

= x2 + 3x + 2.

Explanation:

answer isx2 + 3x + 2.

User Lyana
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.